Assessing the Suitability of Distributed Energy Resources in Distribution Systems Based on the Voltage Margin: A Case Study of Jeju, South Korea - Jun-Hyuk Nam; Seong-Jun Park; Dong-Il Cho; Yun-Jin Cho; Won-Sik Moon (IEEE Access, 2025)
With the growing need for transitioning to clean energy, increasing the share of renewable energy sources has become a global priority. The integration of distributed energy resources (DERs), such as photovoltaic (PV) and wind turbine (WT) systems, is crucial for optimizing the current distribution systems. Despite its benefits, DER integration presents technical challenges. DERs can cause rapid power output changes, leading to voltage instability and overvoltage, thereby impacting the power quality and equipment reliability. Mitigating this instability often requires costly grid infrastructure upgrades. Therefore, optimizing existing networks is essential to reduce these costs. To achieve this, the voltage profile of the target area must be thoroughly assessed and locations suitable for DER integration must be identified to ensure stable operation and voltage stability. This study proposes a new evaluation index, the Voltage Margin Evaluation Index (VMEI), to address the limitations of the existing indices. This index evaluates voltage stability and promotes DER integration in a region. Using the VMEI, we assessed the suitability of DER integration in Jeju, South Korea. Results demonstrate that integrating a 0.5 MW DER at Node 37 in Feeder 5, the optimal point with a VMEI of 1.00066, maintained the maximum voltage at 22.97 kV within the regulated range and improved voltage stability. Conversely, Node 29 in Feeder 4, with the lowest VMEI of 0.97262, resulted in a maximum voltage of 23.84 kV, exceeding the voltage regulation range, demonstrating that VMEI effectively identifies suitable DER integration points. This study provides valuable insights for improving DER integration into distribution systems, aiding the global transition to sustainable energy.